Biological and environmental profiling of three Philippine Tetrastigma species (Vitaceae) in northeastern Cagayan, Luzon, Philippines - JEFF M. OPEÑA; CHARLOT L. MARAMAG; CALIXTO B. ALICAY; MARVIN V. BALOLOY; CLARIBEL A. GASPAR; FROILAN A. PACRIS JR.; JEAN S. TORRES; LYLE B. SUMER; GERLIE U. BAYANI; RACHEL C. SOTTO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Opeña JM, Maramag CL, Alicay CB, Baloloy MV, Gaspar CA, Jr Pacris FA, Torres JS, Sumer LB, Bayani GU, Sotto RC. 2021. Biological and environmental profiling of three Philippine Tetrastigma species (Vitaceae) in northeastern Cagayan, Luzon, Philippines. Biodiversitas 22: 2956-2970. Tetrastigma species have considerable attention because of their medicinal importance, but little is known about these Philippine species. This study provides information on the biological (morphological, phytochemicals, nutritional, antimicrobial characterization) and environmental (diversity, distribution, growing environment, soil characteristics) profiles of the three Philippine Tetrastigma species namely, Tetrastigma ellipticum Merr., Tetrastigma harmandii Planch., and Tetrastigma loheri Gagnep. Tetrastigma harmandii growing in various habitats were widely distributed throughout northeastern Cagayan, while T. ellipticum and T. loheri were found only in the mountain forests of the northernmost part of northeastern Cagayan. Tetrastigma ellipticum was found only in Mt. Cagua forests and volcano, while T. loheri was found growing in the forests of Palaui Island, Buwacag mountain, and Mt. Cagua. Most of the plant species growing within the Tetrastigma environments were native and endemic trees. Mountain species of Tetrastigma (T. ellipticum and T. loheri) grew in extremely acidic soils with high organic matter content. More secondary metabolites were detected in T. ellipticum, which was the only species among the three Tetrastigma species to contain alkaloids, flavonoids, and anthocyanin. Saponins were detected only in T. harmandii. Steroids were not detected in the three species. Moreover, T. harmandii was the only species to have an antibacterial property against Staphylococcus aureus and a slight inhibiting activity against Klebsiella aerogenes. Between the two edible Tetrastigma species, T. harmandii contains more macronutrients and micronutrients, while T. loheri contains higher crude protein, crude fat, and crude fiber.